A Coast-to-Coast Assessment of Cumulative Impacts and Protection Potential in Canadian Marine Conservation Networks - Grace E. P. Murphy; Selina Agbayani; Jocelyn C. Nelson; Emily M. Rubidge; Ryan R. E. Stanley; Cathryn C. Murray; Noreen E. Kelly (Environmental Management, 2026)
The effectiveness of marine conservation networks depends on their ability to manage and safeguard against the many overlapping human activities and stressors influencing marine ecosystems. Cumulative impact mapping (CIM) combines information on the intensity and location of stressors with the spatial extent and vulnerability of marine habitats to generate a single, relative cumulative impact (CI) score. Despite its potential benefits to inform management and conservation efforts, CIM is not commonly incorporated into conservation network planning. Here, we combine published CIMs from the Canadian Atlantic and Pacific bioregions with existing marine conservation areas (MCAs) to compare impacts inside each MCA against regional impacts. We then conduct a scenario analysis to quantify potential reduction in cumulative impacts in two bioregion’s proposed marine conservation networks by modeling the removal of prohibited activities (bottom contact fishing, dredging, disposal at sea) in alignment with the Canadian Marine Protection Standard. Both regions exhibited similar distributions in current CI scores, with approximately half of MCAs scoring significantly above the regional mean, and the other half below. The scenario analysis predicted a 7% mean decrease (range 0–36%) in cumulative impacts across the Scotian Shelf and 2% mean decrease (range 0–17%) across the Northern Shelf networks. We identified 17 MCAs in the Scotian Shelf and 8 in the Northern Shelf as having high protection potential, which can be a valuable decision support tool for conservation planners. We discuss how CIM can be operationalized for conservation network planning and management.